VOCs photocatalytic abatement using nanostructured titania-silica catalysts. Issue 4 (August 2017) - Hussain, Murid; Akhter, Parveen; Iqbal, Javed; Ali, Zulfiqar; Yang, Wenshu; Shehzad, Nasir; Majeed, Khaliq; Sheikh, Rizwan; Amjad, Um-e-salma; Russo, Nunzio
Graphical abstract: Highlights: Nanostructured (1–90%)TiO2 -KIT6 were used for VOCs(ethylene, propylene abatement). (30%)TiO2 -KIT6 showed the best activity and stability for the VOCs abatement. TiO2 uniform dispersion allowed more VOCs adsorption and better light penetration. (90%)TiO2 -KIT6, equivalent to pure bulk TiO2, showed the lowest activity. TiO2 (30%)-KIT6 was further optimized through different calcination treatments. Abstract: In this work, different quantities of TiO2 incorporated into TiO2 -KIT6 nanostructured catalysts were considered to improve the photocatalytic abatement of volatile organic compounds (VOCs; ethylene, propylene) at ambient temperature. The best optimized activity and stability of the catalysts toward(s) ethylene and propylene degradation has been shown for 30 wt% TiO2, while the worst conversion has been observed for a 90 wt% TiO2 loading. This was likely due to the dispersion and stabilization of the anatase TiO2 with 30 wt% on KIT-6, which in turn allowed more VOCs adsorption and better light penetration than 90% TiO2 /KIT-6 in which it showed a bulk phase and large agglomerates with light penetration limitations. VOC abatement has been found to be not only influenced directly by the dispersed TiO2 contents but also by the calcination temperatures, and 500 °C has been found to be the best calcination condition to achieve the highest propylene conversion. The optimized nanostructured photocatalyst developed for ethylene and propylene, could also be promising candidate for other VOCs and different applications.